Evaluating the Feasibility of Sustainable Seafood Labelling Programmes in Small Island Developing States: A Pilot Study of Artisanal Fisheries in Seychelles - Glass, Jessica R.; Belle, Kalsey; Berke, Gregory; Bodin, Nathalie; Burt, April J.; Duncan, Murray I.; Morgan, Sian K.; Pillay, Pavitray; Talma, Sheena (Frontiers in Marine Science, 2022)
The Republic of Seychelles is one of six African Small Island Developing States (SIDS) and has a marine-based economy reliant on fisheries and international tourism. Seychelles has been flagged by the United Nations as highly vulnerable to climate change. Climatic threats are compounded with population declines of key fishery species. A progressive national stance towards ocean sustainability and an emerging economy partially driven by tourists are two of several factors that make Seychelles a good candidate for a sustainable seafood labelling and consumption programme, which would provide market-based incentives for fishery harvesters, regulators, buyers and consumers to improve sustainable practices. To address the feasibility of such a programme, we conducted a pilot study, surveying 33 artisanal fishers and mapping supply chain structure to examine incentives and challenges. Questions addressed fishers’ years of experience, reliance on fishing for income, and flexibility in gear type and species targeted. Of the total number of respondents, 64% would like to see a programme implemented but only 34% thought it would be successful. Participants identified several barriers and benefits that primarily spanned socioeconomic and regulatory themes. Our pilot results indicate the sociocultural and economic impacts of sustainability programmes in Seychelles are as important as environmental considerations, a finding pertinent to anyone undertaking similar research efforts in other SIDS. We advocate for the necessity of thorough, location-based research and in-depth stakeholder consultation to elucidate economic, societal, behavioural and cultural factors that will affect the success of designing and implementing seafood labelling programmes in SIDS.